Human sensory neurons derived from pluripotent stem cells for disease modelling and personalized medicine - Lampert, Angelika; Bennett, David L.; McDermott, Lucy A.; Neureiter, Anika; Eberhardt, Esther; Winner, Beate; Zenke, Martin (Neurobiology of pain (Cambridge, Mass.), 2020)
In this concise Mini-Review we will summarize ongoing developments of new techniques to study physiology and pathophysiology of the peripheral sensory nervous system in human stem cell derived models. We will focus on recent developments of reprogramming somatic cells into induced pluripotent stem cells, neural differentiation towards neuronal progenitors and human sensory neurons. We will sum up the high potential of this new technique for disease modelling of human neuropathies with a focus on genetic pain syndromes, such as gain- and loss-of-function mutations in voltage-gated sodium channels. The stem cell derived human sensory neurons are used for drug testing and we will summarize their usefulness for individualized treatment identification in patients with neuropathic pain. The review will give an outlook on potential application of this technique as companion diagnostics and for personalized medicine.
Created from Fastlane, Scopus look-up
Keywords: Disease modelling; iPSC; Pain; Peripheral neuron; Stem cell differentiation